Implementation of Enhanced Re-Engineering on Trivia Game to Improve Immersion - Adryan Nur, Fathur; Nuryasin, Ilyas; Wibowo, Hardianto (Journal of Games, Game Art, and Gamification, 2024)
Trivia games are one type of educational game that is in great demand and can be used as a medium of entertainment as well as a learning medium. In order to make a game in the same segment more unique and immersion, software re-engineering techniques are used in the trivia game. In re-engineering the trivia game, three methods are used: Enhanced Re-Engineering as a software re-engineering method; Game Development Life Cycle (GDLC) in the development of the Hidden Object Trivia game; and MEEGA+ as a testing method for the trivia game and the Hidden Object Trivia game to determine the increase in immersion value of the two games. The results of re-engineering the Tech Geek Quiz game led to the successful integration of trivia and hidden object genres, resulting in the creation of the Guess The Tech Tool game. The test results using MEEGA+ with 30 respondents showed an increase in immersion values of 50.26% from 1.89 to 2.84 in the usability factor and 30.29% from 2.08 to 2.71 in the player experience factor. The results were taken from all dimensions of the questions that had been asked.